Are We Past the Heterosexual Script? A Content Analysis of Contextual Cues Within the Heterosexual Script in Tween, Teen, and Young Adult Television Programs. Issue 3 (4th May 2022) - Terán, Larissa; Roberts, Lindsay; Yan, Kun; Aubrey, Jennifer Stevens
ABSTRACT: In light of recent research establishing the prevalence of the heterosexual script on television (Aubrey et al., 2020; Kim et al., 2007), the present study investigated the context of the heterosexual script in 182 episodes of tween, teen, and young adult television programs. The following scripts were assessed: sex as masculinity (masculinity is achieved through sexuality), good girls (women are sexual gatekeepers), male commitment (men avoid commitment), and female commitment (women seek commitment). Results revealed that depictions of the heterosexual script varied with sexual behavior, sexual talk, and the composition of gender in conversation dyads but not with the gender of sexual initiators. Sex as masculinity was most likely to occur with intimate touching, talk about sexual interests, and mostly discussed within female-female dyads. The good girls script was most likely to occur with instances of intimate touching and talk about sexual advice, whereas male commitment was most likely to occur in portrayals of intercourse and talk about sexual experiences. Lastly, female commitment was most likely to occur in talk toward sex and in male-male dyads.